Numerical simulation of fatigue crack growth based on accumulated plastic strain. (August 2020) - Borges, M.F.; Neto, D.M.; Antunes, F.V.
Highlights: FCG by node release occurs when accumulated plastic strain reaches a critical value. A critical plastic strain of 110% was obtained for the 2024-T351 aluminium alloy. The da/dN-ΔK curve was found to be linear in log-log scales with a slope m = 2.4. The difference to experimental results was attributed to mechanisms activated at high loads. A good agreement with experimental results was found for the 18Ni300 maraging steel. Abstract: Fatigue crack growth (FCG) is simulated here by node release, which is made when the accumulated plastic strain reaches a critical value. The numerical procedure is very robust, showing a very fast stabilization and independence relatively to the load considered for node release. A critical accumulated plastic strain of 110% was obtained for the 2024-T351 aluminium alloy, comparing the experimental value of da/dN for a crack length of 26.5 mm and a stress ratio of 0.1, with plane strain numerical predictions. This critical value was used to predict da/dN for different crack lengths. The da/dN-ΔK curve was found to be linear in log-log plot with a slope m = 2.4, which is lower than the slope m = 3.6 presented by the experimental results. The difference is attributed to crack tip mechanisms activated at relatively high loads. The variation of stress ratio and stress state did not affect the da/dN-ΔK curves, which indicates that the effect of these parameters is not linked to crack tip plastic deformation. FCG rate was also predicted for the 7050-T6 aluminium alloy and the 18Ni300 maraging steel, and slopes m = 3.09 and 2.70, respectively, were obtained for da/dN-ΔK curves. The predictions obtained for the steel agreed well with experimental results.